SISTEM INFORMASI DAN REKOMENDASI PENJUALAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Darwin Raharja; Desi Arisandi; Novario Jaya Perdana (Fakultas Teknologi Informasi Universitas Tarumanagara, 2022)
PD. Prima Karya Busana is an embroidery service provider since 2006 but more modern competitors have emerged. The COVID-19 pandemic has also forced digitalization activities. With this sales information and recommendation system, customers don't need to come and order manually, which can be done via the web as well as reach out to potential customers. There is a recommendation feature that can be used by customers to determine the selection of the best type of embroidery fabric based on several criteria such as price, weight, absorption rate, level of smoothness, clarity of embroidery stitches, and material resistance through interviews with PD. Prima Karya Busana owner using Simple Additive Weighting method. The method used for web development is System Development Life Cycle with Rapid Application Development model. The programming language used is PHP and MySQL as the database. The development has been completed properly based on Blackbox Testing and in accordance with the PD. Prima Karya Busana owner based on User Acceptance Testing and feedback provided. Customers and prospective customers are also proven to be able to access the web online well and use the recommendation feature to choose the best type of embroidery fabric based on the User Acceptance Testing.